The main epistomological assumptions of contemporary biology (a survey) - Pakszys, Elżbieta (Theoria et Historia Scientiarum, 2007)
Cognitive condition of any scientific domain depends on its location among other fields of study, since relationships with the closest „neighbors” supplies, so it seems, fruitful analogies in executing the most important scientific functions: description, explanation and pre/postdiction. This way acquired interdiscip¬linary knowledge has its contribution in the ideal of objectivity, most crucial in creating the image of fully matured science. This does not mean however, that we are dealing with the relationships abandoned of any limits between different scientific disciplines today. Quite contrary, specialization, peculiarity or autonomy of study seems to be equally justified feature of every advanced research, acquired especially through different methods and interpretation, invented and applied to various objects of study. Certainly, both reciprocal currents tend to shape contemporary research in all natural history. In this essay however, I will try to indicate only these concerning biology.